Disability and Poverty 2011
DOI: 10.2307/j.ctt9qgths.8
|View full text |Cite
|
Sign up to set email alerts
|

Living conditions among people with disabilities in developing countries

Abstract: Living conditions and poverty are two common quantifiers or parameters of socioeconomic status and both have evolved from rather narrow economic and material concepts to encompass broader and more complex understandings.According to Heiberg and Øvensen (1993), studies on living conditions have evolved to include individuals' capabilities and how they utilise their capabilities. Likewise, the concept of poverty has expanded beyond a derived level of income or accumulation of material goods whereby 'poverty is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…In developing countries, studies published in peer-reviewed journals are limited and to our knowledge cover only eight countries. They all find lower employment rates for persons with disabilities (Hoogeven 2005 (Uganda) Expanding to other studies, a similar finding is also found in Eide et al (2003bEide et al ( , 2009 This paper uses a unique data set, the World Health Survey (WHS), collected by the World Health Organization (WHO) in 69 countries with a consistent measure of disability and employment in all countries. This is the first cross sectional international survey conducted to provide reliable and internationally comparable data on disability and this paper is the first systematic study of employment rates across disability status and their determinants in developing countries.…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…In developing countries, studies published in peer-reviewed journals are limited and to our knowledge cover only eight countries. They all find lower employment rates for persons with disabilities (Hoogeven 2005 (Uganda) Expanding to other studies, a similar finding is also found in Eide et al (2003bEide et al ( , 2009 This paper uses a unique data set, the World Health Survey (WHS), collected by the World Health Organization (WHO) in 69 countries with a consistent measure of disability and employment in all countries. This is the first cross sectional international survey conducted to provide reliable and internationally comparable data on disability and this paper is the first systematic study of employment rates across disability status and their determinants in developing countries.…”
Section: Introductionsupporting
confidence: 48%
“…Other studies do find a higher share of workers with disabilities in self-employment compared to workers without disabilities in several countries (e.g. Eide et al (2003Eide et al ( , 2006Eide et al ( , 2009Eide et al ( , 2011b, Loeb et al (2004) and Mitra and Sambamoorthi (2006)). Further research is needed on informal/formal employment across disability status in developing countries.…”
Section: Discussionmentioning
confidence: 98%
“…Alternative service models, including generic rehabilitation workers and communitybased rehabilitation workers, have been used to attempt to meet the needs of PWD, including PWCD. Despite these efforts, only 26 -55% of PWD surveyed across four Southern African nations reported receiving any medical rehabilitation, and the majority of this rehabilitation was reported to be for physical disabilities (Eide & Loeb, 2006;Eide & Yusman, 2009;Eide, Nhiwathiwa, Muderedzi, & Loeb, 2003;Loeb & Eide, 2004).…”
Section: Under-served Pwcd In Majority World Countriesmentioning
confidence: 99%
“…A lower standard of living is reported in households with a person with disability in both rural and urban Nepal. 1 Little is known about the impact of neurodisability among children in Nepal. Our aim was to understand the impact of childhood neurodisability in Eastern Nepal.…”
Section: G292(p) Estimates Of the Burden Of Groupmentioning
confidence: 99%